The effects of main tillage methods on the productivity of maize hybrids in the Left-Bank Forest-Steppe of Ukraine - Hanhur, V.; Rudenko, V. (Scientific Progress & Innovations, 2024)
Maize (Zea mays L.) is one of the three most important cereals in the world. This crop is significant for the economic development of countries where it is oriented to the agricultural sector. The research to study the effect of different methods of basic tillage on the biometric parameters of maize plants and the formation of productivity of maize hybrids of different maturity was conducted in the conditions of the Poltava State Agricultural Research Station named after M. Vavilov during 2019–2020. According to the field experiment, it was found that plants of hybrids DN Patriot, DN Fiesta, DN Julia were characterized by the largest linear parameters for cultivation on the shelf tillage condition. Replacing plowing by 20–22 cm by moldboardless tillage, in particular, flat-cut tillage by 14–16 cm and surface tillage by 8–10 cm, led to a decrease in plant height by 2.8 and 3.4 %, 1.5 and 3.0 %, 2.4 and 0.4 %, respectively. The plant height of the mid-maturing hybrid DN Julia was almost the same both under plowing and surface tillage. It was found that the yield of the early maturing hybrid DN Patriot and the mid-early maturing hybrid DN Fiesta was the highest when they were growing under shelf tillage to a depth of 20–22 cm. In the case of moldboardless tillage, in particular, flat-cut tillage by 14-16 cm and surface tillage by 8-10 cm, a significant decrease in grain productivity was noted, respectively, by 5.5 and 1.9 and 5.1 and 2.2 %. The maximum grain productivity of the mid-maturing hybrid DN Julia was obtained in the variant with surface tillage by 8–10 cm (7.15 t/ha), which is 0.28 and 0.43 t/ha or 4.1 and 6.4 % more compared to flat-cutting and shelf plowing. It was found that on the chernozem soils of the Left-Bank Forest-Steppe of Ukraine, the best biometric parameters of plants and higher grain productivity of the early maturing maize hybrid DN Patriot and the mid-early maturing maize hybrid DN Fiesta (6.17 and 6.93 t/ha) are formed by plowing to a depth of 20–22 cm. At the same time, the reaction of the mid-maturing hybrid DN Julia to this variant of basic tillage was reversed.